Lean ignition and blow-off behaviour of butyl butyrate and ethanol blends in a gas turbine combustor. (1st March 2019) - Zhang, Zhichao; Chen, Longfei; Lu, Yiji; Paul Roskilly, Anthony; Yu, Xiaoli; Smallbone, Andrew; Wang, Yaodong
Highlights: Lean ignition and blow-off of butyl butyrate-based biofuels were reported. Butyl butyrate-based biofuels are easier to be ignited and more difficult to be blown off in a GT combustor were conducted. Two new equations successfully predicting key combustion performance were proposed. Abstract: This paper reports the experimental study on lean ignition (LI) and lean blow-off (LB) behaviour of butyl butyrate-based biofuels in a gas turbine combustor. The butyl butyrate-based biofuels were formulated (butyl butyrate–ethanol blends with the volume percentage of ethanol 0, 10%, 30%, 50% respectively, named BE-0, BE-10, BE-30, BE-50). The aviation kerosene RP-3 was also tested as a reference fuel. A combustor of an aero-engine was fabricated to conduct experiments on these fuels. The statistic method Design of Experiments (DoE) was employed to correlate LI and LB with fuel properties and operating conditions, and then analyse the significance of these experimental variables. The results indicated that all test biofuels had lower equivalence ratio of LI than RP-3, but the LB between RP-3 and the biofuels of high ethanol fraction (30% and 50%) had no appreciable difference at low air flow rate. The results also demonstrated that fuels with high ethanol fractions tended to ignite and blow off the flame at higher equivalence ratios. Meanwhile, the equivalence ratio of both LI and LB decreased at high inlet air flow rate for all the test fuels. RP-3 could combust under a larger range of air conditions yet its stability was more sensitive to air flow rate than test biofuels. Two predictive equations of LI and LB were obtained via Design of Experiments (DoE) and demonstrated that the lower heating value (LHV) of fuels, air pressure drop in the combustor, fuel pressure and inlet air pressure of the combustor were the main factors influencing LI and LB.